Association between sleep characteristics, ideal cardiovascular health, and systemic inflammation, NHANES 2017–2018. (2nd October 2021) - Cash, Rebecca E.; Crowe, Remle P.; Goldberg, Scott A.; Patrick, Casey; Wells‐Whitworth, L. Michael; Barger, Laura K.; Camargo, Carlos A.
Summary: There is conflicting evidence regarding the associations between sleep deprivation and inflammatory biomarkers indicative of cardiovascular disease risk, such as high‐sensitivity C‐reactive protein (hsCRP). The association between sleep habits and hsCRP was quantified in a nationally representative sample of adults in the United States and mediation by ideal cardiovascular health metrics was explored. A cross‐sectional analysis of cardiovascular disease‐free participants aged 20–79 years from the 2017–2018 National Health and Nutrition Examination Survey was conducted. The primary exposures were self‐reported sleep duration, sleep debt (difference between the average weekday and weekend sleep duration), and ideal cardiovascular health (11–14 points). The primary outcome was hsCRP (high‐risk ≥ 3.0 mg/L). Multivariable robust Poisson models were used to estimate prevalence ratios after multiple imputation. A subgroup analysis of shift workers was also conducted. Of 4027 participants included (mean age 46 years; 52% female; 41% shift workers), the prevalence of sleeping <6 h on weekdays was 9%, with 40% sleeping ≥9 h on weekends. One‐quarter had a high (≥2 h) sleep debt, 82% had poor cardiovascular health, and 34% had high‐risk hsCRP. There were no significant associations between weekday sleep duration or sleep debt with high‐risk hsCRP, even among shift workers. Mediation analysis was not conducted. Ideal cardiovascular health was associated with a lower prevalence of high‐risk hsCRP (prevalence ratios, 0.60, 95% CI, 0.48–0.75). The lack of significant associations suggests a complex interrelationship of hsCRP with factors beyond sleep duration. Examination of populations at highest risk of chronic sleep deprivation could help to elucidate the association with systemic inflammation‐related outcomes.